Synthesis, Characterization, and Osteogenic Ability of Fibrillar Polycaprolactone Scaffolds Containing Hydroxyapatite Nanoparticles - Pansani, Taisa N. [UNESP]; de Souza Costa, Carlos Alberto [UNESP]; Cardoso, Lais M. [UNESP]; Claro, Amanda M.; Barud, Hernane da Silva; Basso, Fernanda G. [UNESP] (American Chemical Society (ACS), 2025)
Polymer-based scaffolds for bone regeneration aim to mimic the structure and function of the collagen-rich extracellular matrix. Hydroxyapatite incorporated into these biomaterials improves their mechanical and biological properties due to its bioactive osteoconductive nature. The objectives of this study are to synthesize and characterize polycaprolactone (PCL) scaffolds containing hydroxyapatite nanoparticles (HAn) at 1, 2.5, 5, and 7% concentrations and to determine their cytocompatibility and osteogenic potential. Fiber thickness (n = 240) and interfibrillar space (n = 8) of PCL scaffolds were characterized by scanning electron microscopy (SEM). The PCL scaffolds were evaluated concerning their thermal degradation (TGA), calcium release, and hydrophilicity (WCA). Preosteoblasts were seeded on PCL scaffolds and assessed regarding their viability (AlamarBlue, n = 8), collagen synthesis (SR, n = 8), total protein synthesis (TP, n = 8), alkaline phosphatase activity (ALP, n = 8), deposition of mineralization nodules (MN, n = 8), and cell adhesion (fluorescence microscopy). The data analyses of the biomaterials, including TGA, energy dispersive spectroscopy (EDS), and Fourier transform infrared spectroscopy (FTIR), were interpreted descriptively. The quantitative data were statistically analyzed (α = 5%). Scaffolds without HAn exhibited thicker fibers. The higher incorporation of HAn in the PCL scaffolds increased the interfibrillar spaces and resulted in greater P and Ca peaks (p < 0.05), as well as broader peaks representing the P-O group (FTIR). TGA demonstrated that PCL scaffold degradation was inversely proportional to their HAn concentration. Higher percentages of cell viability were observed with the incorporation of HAn. ALP activity increased in cells seeded onto PCL scaffolds containing 2.5% HAn. Deposition of MN was directly proportional to the amount of HAn incorporated. HAn incorporated into PCL scaffolds interferes with the physicochemical properties of these biomaterials and favors in vitro osteogenesis.
Keywords: biocompatible materials; hydroxyapatite; osteoblasts; osteogenesis; scaffolds